All Days 2009
DOI: 10.2118/127554-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Study of Consolidation Effect on Time Delayed Borehole Stability During Underbalanced Drilling in Shale

Abstract: Time delayed mechanical borehole stability is mostly depending on the pore pressure consolidation process. Establishment of pore pressure equilibrium in shale is a time dependent process which is characterized by shale intrinsic properties i.e., porosity, permeability, fluid and rock stiffness parameter etc. In shale, water movement is greatly restricted by the low permeability of shale which may cause pore pressure storage. The Influence of induced pore water pressure and its dissipation is critical for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Because shale is expected to be anisotropic, it is reasonable to expect the permeability to be anisotropic and to expect the largest values parallel to the bedding. Islam et al (2009) reported that the magnitude of the consolidation time for the finite diffusive length adjacent to the borehole wall was only in the range of hours and days for samples with a permeability of 100 gD. Therefore, drained tests were necessary for time-delayed material failure analysis.…”
Section: Triaxial Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Because shale is expected to be anisotropic, it is reasonable to expect the permeability to be anisotropic and to expect the largest values parallel to the bedding. Islam et al (2009) reported that the magnitude of the consolidation time for the finite diffusive length adjacent to the borehole wall was only in the range of hours and days for samples with a permeability of 100 gD. Therefore, drained tests were necessary for time-delayed material failure analysis.…”
Section: Triaxial Testingmentioning
confidence: 99%
“…For the drained tests, the rate was approximately 2 9 10 -8 s -1 . In addition, the size of the test sample and the time required to perform a test depended highly on the permeability of the shale (Nes et al 1998;Islam et al 2009;Loret et al 2001) and the fluid viscosity.…”
Section: Triaxial Testing Of Shalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of wellbore instability can be classified into either mechanical (i.e., failure of the rock around the borehole because of high stresses, low rock strength, or inappropriate drilling practice) or chemical effects which arise from damaging interaction between the rock and the drilling fluid [4][5][6]. In recent years, wellbore stability analysis has mainly focused on the chemical interaction between rock and drilling fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The 3-D method has had more and more applications in recent years (Islam, Skalle, Faruk, and Pierre 2009;Shen 2009;Shen, Bai, andSmith 2010, Shen 2013). Details of the geostructure, including syncline or anticline, will be taken into account in its calculation.…”
Section: Introductionmentioning
confidence: 99%